"Solo un militare italiano": realismo e modelli di genere nel combat film italiano degli anni Cinquanta - Paolo Noto (Annali Online dell'Università di Ferrara. Sezione Lettere)
The essay focuses on a cycle of combat films produced in Italy in the 1950s, dedicated to the Second World War and directed by filmmakers such as Duilio Coletti and Francesco De Robertis. The relationships between this genre films and the contemporaneous realist culture, usually overlooked by later historians, are redefined in the light of articles and reviews published in film journals and popular magazines at the time, and according to the interpretation of neorealism recently provided by Karl Schoonover as an aesthetic catalyst of a transnational “politics of pity”. This brings to the analysis of the gender roles represented in these films, with a particular attention to the representation of an imperiled yet heroic masculinity.